An assessment of the knowledge, attitudes and practices of caregivers of HIV positive children on treatment in Pretoria, South Africa : a case study of out-patients in Kalafong Hospital, Pretoria - Ofunne, Ifeanyichukwu (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.